Large Wiedemann effect in (Co70Fe30)99.8(NbC)0.2 wires with strong 〈100〉 circumferential texture. (December 2017) - Zhao, Yalong; Li, Jiheng; Bao, Xiaoqian; Mu, Xing; Gao, Xuexu
Abstract: In this work, 0.5 mm diameter magnetostrictive (Co70 Fe30 )99.8 (NbC)0.2 wires were prepared using forging and drawing processes. A Wiedemann twist up to 1348″/cm has been achieved in the annealed wires and to our knowledge is the largest value of Wiedemann effect in magnetoelastic materials. Microstructure analyses of the annealed wires indicate that large Wiedemann twist was attributed to the 〈100〉 circumferential texture and the fcc nanoparticles embedded in bcc matrix. The results indicate that the favorable circumferential texture and heterogeneous structure can be used to guide exploration of materials with large Wiedemann effect. Graphical abstract: